Topographical and Ultrastructural Evaluation of Titanium Plates Coated with PLGA, Chitosan, and/or Meropenem: An In Vitro Study - Mohammad Al-Qubaisey; Rita Khounganian; Abdulhakim Al-Badah; Raisuddin Ali (MDPI AG, 2022)
The present investigation was undertaken to evaluate the topographical and ultrastructural architecture of titanium plates coated with polylactic co-glycolic acid (PLGA), chitosan (CH), and/or meropenem (MEM) with or without Staphylococcus aureus (SA) or Pseudomonas aeruginosa (PA) bacteria. Single-hole segments of 0.4 mm thick, low-profile titanium plates were spray coated using an airbrush with polymeric carriers (PLGA or CH) loaded with MEM, in addition to the negative control group (uncoated titanium plates). The coated plates and the negative control group were subjected to bacterial biofilms through a cultivation process while being slowly stirred at 20 rpm for 24 h. The samples were fixed and processed for scanning electron microscopic study at 5, 10, and 20 k magnification. The data were statistically analyzed to compare within and between the different materials. Coating titanium plates with PLGA or CH with MEM appeared to enhance bacterial inhibition over uncoated plates, hindering biofilm formation and preventing bacterial proliferation. In the staphylococcus aureus group, the highest bacterial count was observed in the uncoated plates, whereas the lowest count was detected in meropenem-PLGA, followed by PLGA, chitosan, meropenem, and meropenem-chitosan, respectively. On the other hand, the Pseudomonas aeruginosa group with the uncoated plates had the highest bacterial count, whereas the lowest bacterial count was found related to CH, followed by PLGA, MP, MC, and MEM, respectively.